The why and how of pulpal pain - Preeti Nair; Priyanka Deepak Deshmukh; Somya Bhavsar; Ganiga Channaiah Shivkumar (Wolters Kluwer Medknow Publications, 2022)
A proper understanding of pulpal pain has been an enigma to the scientific community. While neurons and transmitters are active participants, focus on neuropeptides has not been emphatic. A complex array of interaction of inflammatory substances, with assortment of nerve fibers in the presence of these molecules, has shed some light to this mysterious phenomenon of pulp pain. A literature search was made of the standard textbooks, Google Scholars, Pubmed and Scopus database for review, original research, case control studies using key words like "pulpal pain" and 'chemicals responsible for pain mechanism' . This paper is an attempt at highlighting not only the roles of these proteinaceous materials, so that they could be targeted to eliminate pain, but also the neuro anatomy and neurophysiology of the pulp.